2022
DOI: 10.3390/ijms23105333
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Stress Alters Expression of Glucocorticoid Stress Response Genes and Trophic Factor Transcripts in the Rodent Basal Ganglia

Abstract: Early life stress shapes the developing brain and increases risk for psychotic disorders. Yet, it is not fully understood how early life stress impacts brain regions in dopaminergic pathways whose dysfunction can contribute to psychosis. Therefore, we investigated gene expression following early life stress in adult brain regions containing dopamine neuron cell bodies (substantia nigra, ventral tegmental area (VTA)) and terminals (dorsal/ventral striatum). Sprague–Dawley rats (14F, 10M) were separated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Indeed, there is a striking overlap between stress and reward neurobiology, which recruits the same brain regions including the ventral striatum, amygdala, and medial prefrontal cortex (5,49,50). Moreover, these regions are dense in terms of glucocorticoid receptors (60), which were found to be altered following early life stress exposure in animals (61) and humans (62). Therefore, it is not surprising that we identified that adversities were associated with disrupted EV and PE signaling in the reward network.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, there is a striking overlap between stress and reward neurobiology, which recruits the same brain regions including the ventral striatum, amygdala, and medial prefrontal cortex (5,49,50). Moreover, these regions are dense in terms of glucocorticoid receptors (60), which were found to be altered following early life stress exposure in animals (61) and humans (62). Therefore, it is not surprising that we identified that adversities were associated with disrupted EV and PE signaling in the reward network.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, PFC is also crucial for sensorimotor gating, a brain function differently affected by CN and/or ESI in a sex- and age-dependent manner ( Bratzu et al, 2023 ). Since early postnatal experiences and rearing conditions can induce sexually dimorphic changes in CB1R expression, endocannabinoids and/or corticosterone levels ( Brown and Grunberg, 1995 ; Suárez et al, 2009 , 2010 ; Viveros et al, 2009 ; Dow-Edwards et al, 2016 ; Ramírez-López et al, 2017 ; Portero-Tresserra et al, 2018 ; Caradonna et al, 2022 ; Tran et al, 2022 ; Walker et al, 2022 ) we assessed the effects of CN or ESI in both female and male offspring to detect potential sex differences. Furthermore, the potential impact of CN condition on the effects of early social isolation has been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…These GR primary targets trigger physiological and pathological responses of GCs. Therefore, we used the GR gene expression in VTA (VTA-GR) to investigate the effect of different variable light intensity lighting programs on the welfare of birds as described in other animal studies (Daftary et al, 2009;Mizoguchi et al, 2021;Tran et al, 2022). The lower level of GR in 20-lx-and VL-treated birds indicates that the VTA-DAergic system is necessary to initiate fear extinction and reveal a crucial role of DA neurons in this form of safety learning.…”
Section: Regulation Of Welfare-indicating Genes and Melanopsin (Opn4)...mentioning
confidence: 99%